Application of instrumentation in cotton cultivation: systematic literature review (Research, Society and Development, 2022)
The present work aims to carry out a Systematic Review of the Literature, in order to understand the use of instrumentation applied to cotton cultivation. For this purpose, a search was carried out in four databases and the StArt software was used for data analysis and selection of works. For a total of 1,914 works obtained from the databases, 30 were selected based on selection criteria for full reading. In the end, it was concluded that the works have several applications, mainly related to the classification of cotton for the industry, in addition, the work also pointed out a great possibility of investment and application of instrumentation in cotton culture at various stages of its production chain.